Empirical Evaluation of Work Environment Based on Transportation Factors at Brawijaya University - Purwanto, Imam Nurhadi; Abusini, Sobri; Zulkarnaen, M. Naufal Reza; Pandapotan, Daniel; Talib, Taufan (Green Publisher Indonesia, 2025)
The rapid growth of universities has created a complexity of campus transportation issues that impact the quality of the working environment of the academic community. Inadequate parking facilities and heavy traffic conditions are crucial issues that require empirical evaluation to support appropriate policy making. This study aims to empirically evaluate the effect of parking facilities and traffic conditions on the impact of the work environment at Brawijaya University. Structural Equation Modeling - Partial Least Squares (SEM-PLS) approach is used to analyze the relationship between latent variables and indicators that are not directly measured. Data was collected through a survey to the academic community of Universitas Brawijaya. The results of SEM-PLS analysis prove that parking facilities and traffic conditions have a significant influence on the campus work environment, both directly and indirectly. Traffic conditions proved to have the most dominant direct influence on the work environment, indicating that the smooth flow of campus traffic is a major determinant of the quality of the work environment of the academic community. In addition, based on the dominant influence of traffic conditions, Brawijaya University needs to prioritize investment in an integrated campus traffic management system.